Implementation risk factors of collaborative housing in Poland: The case of 'Nowe Zerniki' in Wroc±aw - Piotr Lis; Zuzanna Rataj; Katarzyna Suszyńska (Journal of Risk and Financial Management, 2022)
The main aim of this study is to elucidate implementation risk factors of collaborative housing in Poland. The research is based on Rogers' framework supported by Kim and Mauborgne's utility map. On this basis, in-depth interviews were carried out with the leader of a housing project called 'Nowe çZerniki' in Wroc±aw, residents of collaborative housing, third sector actors, architects and researchers. An analysis of potential demand for collaborative housing was conducted using focus groups for a selected group of students who will make housing choices in the coming years. In their work, the authors assess the factors inhibiting the rate of diffusion of collaborative housing in Poland, point out the utility constraints and try to formulate the basic conditions for socio-technical transitions in the area of grassroots housing. The results indicate that collaborative housing in Poland requires a friendly and supporting environment, credit institutions with experience in handling innovative housing projects and experienced leaders. The connection to the place and the local capital are crucial factors for all the key actors of the collaborative housing process.
Keywords: 330; collaborative housing; diffusion of innovations; utility maps; Poland